Instilling Anti-Corruption Spirit Early on: An Sociological Juridical Review of Anti-Corruption Education that Grows among Students in the City of Semarang, Central Java - Edytya, Nindya Putri; Annisa, Annisa (Law Research Review Quarterly, 2019)
White Collar Crime or Corruption is no longer a foreign matter in the government of the State of Indonesia. Like a culture that is rooted and continues to evolve, the problem of corruption in Indonesia has not yet found a bright spot, all the resources and efforts continue to be deployed to eradicate the already chronic disease in the body of this country. In 2018, the International Transparency Organization launched data on the Corruption Perception Index (CPI). Based on these data, Indonesia was ranked 89th with a score of 38. The government is well aware that this problem is no longer an ordinary problem, but has become an entrenched culture even to the line of life of the Indonesian people, this certainly requires us to work harder to eradicate this disease to its roots. Based on this, the author argues that in an effort to solve the problem of corruption is not enough if we only rely on law enforcement officers. There is another aspect that the writer values ​​are very important in fighting this problem, that aspect is education. Eradication of corruption in the aspect of education can be applied as a preventive step, namely by instilling the value of honesty and justice in the souls of students. Based on this, the author took the initiative to conduct a research with a sociological juridical approach in the city of Semarang, Central Java.